ANALYSIS OF FINANCIAL STATEMENT OF STAR CEMENT LIMITED - Sahinujjaman (EPRA International Journal of Economic and Business Review(JEBR), 2023)
This study is totally related to financial management and its growth in Star Cement limited. It explains all advantages and objective of the financial management. The objective decides To know the sources of finance and uses of finance, To compare the balance sheet and profit & loss statement of different years, To assess the liquidity position and solvency position. Time frames of the study are 5 years financial statements of Star Cement limited from 1st April ’2013 to 31st march, 2018.